Gendered Life-Course Patterns in Post-Socialist Romania: An Illustration from Households Situated in Precarious Prosperity. Issue 1 (2nd January 2018) - Vlase, Ionela; Preoteasa, Ana Maria
Abstract: This paper documents the gendered aspects of changes affecting the life course of Romanians post-socialism, and the meanings men and women—with ages spanning across various age cohorts—employ to make sense of their experiences. Based on qualitative data collected during research on precarious prosperity among Romanian households conducted in 2013, the findings show that major shifts occurred in the timing of life events. Romanians' life courses and their work trajectories have been unevenly affected depending on their intersectional belonging to gender, area of residence and life stage at the moment of the political transition. The analysis of work trajectories unravels increasing gender differentiation among younger cohorts and reinforcement of the gendered life paths taken.